A 3D microstructured cohesive–frictional interface model and its rational calibration for the analysis of masonry panels. (September 2017) - Serpieri, R.; Albarella, M.; Sacco, E.
Abstract: A 3D microstructured composite Interphase Formulation (IF) based on a Multiplane Cohesive-Zone Model (M-CZM) is proposed for describing the behavior of quasi-brittle joints. The IF is devised so as to reproduce an initial linear elastic behavior, corresponding to the elastic parameters of a thin layer of finite thickness and stiffness, followed by a post-elastic response of the joint featuring progressive crack formation and onset of frictional and dilating responses. All nonlinear features of the joint response are determined by a zero-thickness multiplane-CZM accounting for the development of a microstructured crack inside the joint. The paper proposes a consistent and reproducible calibration procedure of the model parameters for its employment in the simplified micro-modeling of masonry joints. A numerical-experimental assessment of the predicted flexural response of masonry wallettes is presented, employing as a source for material parameters the data available from the experimental campaign of van der Pluijm and coworkers on the meso-scale response of units and mortar joints. The data from the structural bending tests on masonry wallets of the same campaign are used next to assess the simulated structural response following a blind-like approach, i.e., avoiding fine tuning of the mesoscale model parameters on the basis of experimental structural data on masonry wallettes. The numerical-experimental comparison appears to be satisfactory.